Integrating single cell transcriptomics and volume electron microscopy confirms the presence of pancreatic acinar-like cells in sea urchins - Paganos, Periklis; Ronchi, Paolo; Carl, Jil; Mizzon, Giulia; Martinez, Pedro; Benvenuto, Giovanna; Arnone, Maria Ina (Frontiers in Cell and Developmental Biology, 2022)
The identity and function of a given cell type relies on the differential expression of gene batteries that promote diverse phenotypes and functional specificities. Therefore, the identification of the molecular and morphological fingerprints of cell types across taxa is essential for untangling their evolution. Here we use a multidisciplinary approach to identify the molecular and morphological features of an exocrine, pancreas-like cell type harbored within the sea urchin larval gut. Using single cell transcriptomics, we identify various cell populations with a pancreatic-like molecular fingerprint that are enriched within the S. purpuratus larva digestive tract. Among these, in the region where they reside, the midgut/stomach domain, we find that populations of exocrine pancreas-like cells have a unique regulatory wiring distinct from the rest the of the cell types of the same region. Furthermore, Serial Block-face scanning Electron Microscopy (SBEM) of the exocrine cells shows that this reported molecular diversity is associated to distinct morphological features that reflect the physiological and functional properties of this cell type. Therefore, we propose that these sea urchin exocrine cells are homologous to the well-known mammalian pancreatic acinar cells and thus we trace the origin of this particular cell type to the time of deuterostome diversification. Overall, our approach allows a thorough characterization of a complex cell type and shows how both the transcriptomic and morphological information contribute to disentangling the evolution of cell types and organs such as the pancreatic cells and pancreas.